h y Maurits W. Ertsen. - Ertsen, Maurits W.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
The typical image of the Gezira Scheme, the large-scale irrigation scheme started under British colonial rule in Sudan, is of a centrally planned effort by a central colonial power controlling tenants and cotton production. However, any idea(l)s of planned irrigation and profit in Gezira had to be realized by African farmers and European officials, who both had their own agendas. Projects like Gezira are best understood in terms of continuous negotiations. This book rewrites Gezira$1 (Bs history in terms of colonial control, farmers$1 (Bactions and resistance, and the broader development debate.s
Keywords: History; History, Modern; Africa -- History; Africa, North -- History; Great Britain -- History; Imperialism; History; African History; History of Science; History of Britain and Ireland; History of North Africa; Modern History; Imperialism and Colonialism; Electronic books